Parametric Study for the Treatment of Cetirizine Simulated Wastewater Using Electrochemical Methods - Agnihotri, Shivani (My University, 2018)
Pharmaceuticals are consumed worldwide for the treatment and prevention of human and animal diseases. The presence of pharmaceutical compounds in waters poses a potential eco toxicological risk. Due to the low pharmaceuticals removal efficiency of traditional wastewater treatment plants concerns calls are raised for efficient and eco-friendly technologies. Electrochemical advanced oxidation processes, such as electro-floatation, electro-oxidation, electro-coagulation and electro-Fenton attracted a growing interest over the last two decades, to achieve almost complete destruction of the pollutants studied. Cetrizine is an antihistamine widely used for allergic problems, it is a stable drug and very difficult to remove from water. The present study involves parametric study of electro-oxidation and electro-fenton processes for the degradation of cetrizine simulated wastewater. Electro-oxidation and electro-fenton studies were performed on cetrizine containing wastewater with RuO2 coated Ti electrode (Ti/RuO2). The selected operational parameters for electro-oxidation process were pH, cetirizine concentration (CCE), current (i) and time (t) whereas, the selected operational parameters for electro-fenton process were cetirizine concentration (CCE), fenton reagent concentration (CFE), current (i) and time (t). % degradation was selected as a response for the optimization of process parameters. Optimization was performed by using RSM with desirability function. The optimum parameters obtained for EO process at CCE=30ppm were pH=7.09, t=100minutes and i=0.93 A. The optimum parameters obtained for EF process at CCE=30ppm were CFE=0.39mMol, pH=3, t=90minutes and i=1.03A. At the optimum conditions the % degradation was found to be 63.86% for electro-oxidation process and for electro-fenton the % degradation was 77.27% for reaction time of 100 minutes and 90 minutes respectively. The energy consumption for the EO process was 21.7 Wh whereas for EF was 20.87 Wh. Therefore, EF is comparatively economical than EO process. The results were verified by the experimental results. A close relationship was observed between the predicted and experimental results.
Keywords: Cetirizine; RSM optimisation; electro-oxidation (EO); electro-fenton (EF); Degradation efficiency